Ekolojik Planlama İlkelerinin Uygulanmasında Arazi Kullanım Politikalarının Belirlenmesi Ve Esenyurt Örneği Üzerinde İrdelenmesi - Kolay, Hicran (Fen Bilimleri Enstitüsü, 1995)
Çalışmanın konusu; günümüz kentlerinde yaşanan ve her geçen gün artarı çevre sorunlarından ve mevcut planlama pratiğinin buna etkisinden yola çıkarak seçilmiştir. Çalışmanın amacı, çevre sorunlarının öevreye zarar vermeyen ve mevcut sorunları çözebilecek, doğa ile uyumlu kentleri amaçlayan, Ekolojik Planlama, arazi kullanım politikalarının belirlenmesidir. Ekolojik planlama ilkelerinin belirlenebilmesi için, mevcut planlama politikaları irdelenmiş ve birbirleriyle karşılaştırılmalardır. Ayrıca, İstanbul'un bir beldesi olan Esenyurt, bu iki planlama sistemi açısından incelenmiştir. Katılımın, Ekolojik Planlama sistemi içersinde önemli olması nedeniyle, Esenyurt'ta yaşayanlarla bir anket çalışması yapılmıştır. Çalışmanın sonucunda, Ekolojik Planlama prensipleri oluşturulmuş ve bu konuda halk katılımının önemi ortaya çıkmıştır.

Determination of Land Use Planning Policies for Ecological Planning Principle Practices and A case Study of Esenyurt The starting point of this study is the environmental problems that we face in our cities and the effect of these problems on the traditional planning practices. The aim of this study is to determine land use policies of ecological planning, which would help the cities to live in harmony with nature. This study consists of 6 sections: Parti- Introduction is made in this section. The aim and the method used in this study is explained. Part 2: The traditional planning theories and processes (classical planning, comprehensive planning, action planning, particpative planning) are explained and critisized. The Classiccal Planning Theory arranges the phyisical development ofcities and shows where every function will be placed. These functions are shown on maps of various scales. This kind of urbanism is the process in which cities are planned as to take the physical form aimed for the future and to take the necessary measurements to reach this aim. The negative aspects of Classiccal Planning: -Classiccal Planning is a static approach and provides a static view of the future. -Most of the plans has ignored the important role of social and ecenomic factors. -No alternatives can be offered. -Zoning, the main means of implementation ofClassical Planning, is restrictive. -The planner sees him/herself as just a technical staff. This means that the. political role of plans and planners are not considered. Becaise of this, it is hard to make people and politicians to adopt the plans. Comprehensive Planning Theory aims to include the socio-economic aspects and to think of the planning area and the surroundings comprehensively. Comprehensive Planning has joined the technical characteristics and the social benefits of the planning process. But this characteristic has been critisized by social scientists. Above being phyisical, Comprehensive Planning is economical and administrative and includes the implementation pf the plan. After being critisized a lot, many countries have left using it and new theories are practiced in their place. Action Planning is a planning, imlementing process which aims to exceed the problems of classical planning. It emerged from the need of a plan for the Developing Countries which is more elastic and dinamic. In Action Planning, planning and implementaion is joined and they work together. The first reason for the bringing up of Action Planning Theory was tto find operational solutions to the rapid change of situations and to direct the settlements' organization. Action Planning should not be seen as the opposite of long term planning because if so, than it will end up with a planning which is different from the general plan. Participative Planning can come to life with the participation of people and groups to the planning process. Today, the planning systems which ignore the peoples participation brings up many kinds of problems like economic problems, migration problems, environmental pollution, and health problems. To develop environmental awareness on individuals, civil social organizations should be establised beginning from the scale of neigborhoods. And these social organizations should be in touch and in solidarity with each other. XI Part 3: The traditional planning theories and definitions of environment are argued on the example of Türkiye. Most important development in Türkiye, about environment is the economic Law about the Environment that came to operation and th& establishment of The Ministry Of Environment in 1983. With this law the terms "environmental protection", "polluter", "ecologic balance", "waste" entered the Turkish laws. Besides, with this law, "The Water Pollution Control", "Solid Waste", "Noise", "Air Pollution" and "Environmental impact Assessment" Statutes came into operation. Because the Ministry of Environment is newly established, and not enough financed and the inadequency of local units the impelemntations on environmental solutions has not come to an important level. Part 4: The definitions like ecology, ecosystem, and urban ecology are made and the approach to these concepts are given. Different types of problems that cities face (air, water, and noise pollution, energy consumption, traffic congestion) are examined. Solutions developed for solving these problems, like ElA's (Environmental Impact Analysis) are expressed. Urban ecology is the study of urban ecesystems. The city as a whole can be decribed as ecosystems. And human activities are part of these systems. Extraction of resources beyond the capacity of the environment to replace them gesults in resource depletion. Pollution of the environment occurs when methods used in extacting, processing, distributing and consuming resources creates wastes that are discharged into the land, air and water. Urban ecology, does not include all activities in urban areas. Urban spesific problems mostly emerge from consuming natural resources rather than production. The particularly important urban specific problems are: -the overall structure of the area, -the plan for separate blocks or districts, -the transportation system, -waste disposal, -water supply and sewage systems, -noise pollution, -air pollution, xii -organizational solutions which should situmulate the inhabitants to take responsibility for common environmental value. While concentrating on individual problem areas, it is important not to ignore the fact that the urban system is a comlex and is interrelated as a whole. The solution of a problem is might become the reason of another. Sustainable development is the process of equitable economic,; social, cultural and technological improvement in a way that does not pollute ecosystems and deplete natuaral resources. The definition given by WCED for Sustainable Development is "a, pattern of development that meets the needs of present generations without jeopardizing the ability of future generations to meet their own needs. The Environmental Impact Assessment is the response of the growing environmental awareness, increasingly focused on the interactions between development actions and their environmental consequences, since 1950's. This has led to the public demanding that environmental factors be explicitly concidered in the decision making process, in developed countries. A new evaluation approach which came to be known as Environmental Impact Assessment developed. The concept of Environmental Impact Assessment was also seen by the environment lobby as a potentially useful tool to assist their cause. It has evolved as a comprehensive approach to evaluation, in which environmental considerations, as well as economic and technical considerations, are given their proper weight in the decision making process. Part 5: In this part, tha traditional planning principles and ecological planning principles are compared on the example of Esenyurt. According to the traditional planning principles, settlements are planned on the economic and technological measurements. On the contrary Ecological Planning aims settlements planned in the environment and in harmony with the environment. In Traditional planning, settlements are accepted as technical systems having specific functions. As a result the economic productivity of input-out put measurements are important. As for the Ecolegical Planning, it is accepted as an organic system which can live together with the animal and plant life, which is dinamic and which can renew itself with a continious development. Xlll Traditional Planning systems reflect the principles of functionalism, while Ecological Planning accepts proximity between functions. Esenyurt reflects the traditional planning principles and Ecological Planning Principles are ignored. Part 6: A public survey was developed to question the conciousness of the people living in Esenyurt. It was tested on 200 households and 925 people. It was seen that there is an important problem of water supply and sewage systems. But there is not much problem of air and noise pollution. The ones which don't think that there is air pollution are 52.5 %. The discomfort that stems from the water supply problems are 82% and from the sewage system is 64%. 44% of the people living in Esenyurt think that the most important factor for solving environmental problems is local administrations like municipalities must give more attention to these problems. 32.55 of the people living in Esenyurt think that the second important factor for solving environmental problems is the conciousness of the people. Another important result of the survey is that Esenyurt seems to be sufficient in terms of empoyment, services and other functions, but this roots from the economic and cultural level of the people living in Esenyurt. As a result of this survey it can be said that the people living in Esenyurt are aware of some of the environmental problems around them. But these are the problems which they are directly living in. They do not know much about the problems they are not in touch with. And they do not know much about the solutions to the problems. As the conclusion, it can be said that to reach to settlements that live in harmony with the environment without giving any damage to it, the ecological planning principles must be impemented. This planning system can be reached in time by adding new methods, support and that enrich the Traditional Planning system.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1995
Keywords: Arazi kullanımı; Land use; Istanbul-Esenyurt; Ecology; İstanbul-Esenyurt; Ekoloji